Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Orang Pribadi di Kota Jambi - Senusi, Novita; Tiswiyanti, Wiwik; Jumaili, Salman (Ekonomis: Journal of Economics and Business, 2024)
Currently, taxes are the main source of funding for the Indonesian government. In reality, tax sector revenues represent only a small portion of total revenues. In order for the government to implement development projects in Indonesia, taxpayers must pay their taxes on time. The aim of this research is to determine the variables that influence individual taxpayer compliance in Jambi City. This research uses multiple linear regression analysis as data analysis. The results of the research show that simultaneously and partially individual taxpayer compliance is influenced by tax amnesty, tax sanctions, and tax knowledge in Jambi City